Genetically engineered microbial electrocatalysts for high performance biofuel cells - Tao, Le (2017)
Nowadays, the sustainable treatment and exploitation of wastewater is obtaining extensive studies because of the increasing deficiency in water resources, shortage of fossil fuel, and pollution in water. So far, most conventional wastewater remedy procedures need energy and also bring about the issues of pollutants. The microbial fuel cell (MFC) is one type of microbe-catalyzed fuel cell that is able to transfer the energy in chemical form directly from an inorganic or organic materials into electricity by means of a series of bio-chemical reactions. Electricigens are the crucial factor that controls the entire microbial fuel cell performance by means of their metabolic activities and extracellular electron transport (EET). Electron export from the microbial metabolism of the electricigen itself to the anode is carried out by two major ways, that is, direct electron transport as well as mediated electron transport, dependent upon whether the electron shuttles are used in these systems. The extracellular electron transport efficiency is regulated by the voltage difference between the electron donor and the anode acceptor. Both the cell inner and outer membrane and the cell respiratory chain protein complex provide the reacting place for MFC to extract energy from microbes. These electrons are then exported to the anode either through the direct electron transport by c-cytochromes at the inner and outer membrane of the microbes as well as by conducting pili, or through the mediated electron transport induced by electron shuttles. The electron transport is considered as the main constraint condition that restrains the output performance of the microbial fuel cell. The electron shuttle induced electron transport is one of the most widely used electron transport routine for a lot of electricigens. In this work, we recombine the Escherichia coli BL21 (DE3), a strain commonly utilized to express proteins, in order to upregulate the secretion of electron shuttles so that after immobilizing it as the bio-cocatalyst beads, the current and power output of MFC could be raised by more than 9-fold. Then, we overexpress the type two NADH dehydrogenase in the inner-membrane of the electricigens to accelerate electron trans-inner-membrane motion to bridge the gap between substrate oxidation and electron transport of microbial electrocatalyst. The power density of mutant strain increases by 3.3-fold. Thirdly, we coexpress the MtrCAB electron transport protein conduits from wild-type Shewanella oneidensis MR-1 strain as well as the ribAB genes which encodes the first two step of RF biosynthesis in the E.coli BL21(DE) strain so as to improve the power density of E.coli-catalyzed MFCs by 26-fold.